2011
DOI: 10.1074/jbc.m110.209973
|View full text |Cite
|
Sign up to set email alerts
|

Human SREBP1c Expression in Liver Is Directly Regulated by Peroxisome Proliferator-activated Receptor α (PPARα)

Abstract: Sterol regulatory element binding proteins (SREBPs) regulate the expression of a number of enzymes, which catalyze the synthesis of fatty acids, cholesterol, triglycerides, and phospholipids. SREBP1c is the most relevant isoform in the adult liver, and its expression is controlled by the nutritional state. Transcriptional regulation studies into the SREBP1c gene, performed in the last few years, have improved our knowledge of the variability of signals that converge on its promoter region. Insulin, cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 36 publications
2
92
0
Order By: Relevance
“…Irbesartan upregulates hepatic expression of PPAR-α (25) and hepatic SREBP1c expression is directly regulated by PPAR-α (26). The present study also showed upregulated PPAR-α gene expression.…”
Section: Discussionsupporting
confidence: 57%
“…Irbesartan upregulates hepatic expression of PPAR-α (25) and hepatic SREBP1c expression is directly regulated by PPAR-α (26). The present study also showed upregulated PPAR-α gene expression.…”
Section: Discussionsupporting
confidence: 57%
“…The lipogenic transcription factor, SREBP-1c, plays a crucial role in regulating fatty acid synthesis, and SREBP-1c-responsive major genes encode a rate-limiting enzyme in de novo fatty acid biosynthesis. [33][34][35][36] SREBP-1c is activator of the complete program of cholesterol and fatty acid synthesis in the liver. Thus, Ang-(1-7) can have an effect on de novo lipogenesis and lipid metabolism in liver.…”
Section: -13mentioning
confidence: 99%
“…It is known that activation of PPAR under dyslipidemic condition modulates the expression of transcriptional factors SEBP1-c (sterol regulatory element binding protein-1) and ChREBP (carbohydrate regulatory element binding protein), which regulate almost all genes involved in biosynthesis of FA, TAG and phospholipids [22,23]. According to the data that we have already obtained (compensatory action of NSE on the liver phospholipid and fatty acid composition of rats with IR), we suggest Values represented mean ± SEM.…”
Section: Resultsmentioning
confidence: 99%